Analisis Kritik Sastra Feminis dalam Cerpen Catatan Hati Yang Cemburu Karya Asma Nadia - Suaibatul Aslamiyah; Suci Nadilla; Cindy Aprilia Pratami (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2020)
Art has opened the eyes of the world throught literary works that record the history of a writing. Also the subject of women’s affairs is subject to an author’s reference to the problem of a sense of injustice. Such views have been discussed to voice gender equality and to seek efforts to overcome those problems. Nadia’s asthma is one of the authors who attempt to awaken women to the patriarchate system that has been going on. His works consistently incorporate such universal values as equality in various fields, human freedom, and tolerance so that his readers can adopt the value of life. In addition, she was actively involved in social media as a means of channeling her mind. The twitter feed says some of the people were repressed. Seeing the account encourage him to make a book and then be poured into a storybook of several different stories and in which one of the women’s true account t with the tittle of a jealous heart note. The study used qualitative descriptive methods with the theory of feminist literary criticism.